Application of Taguchi approach to optimize friction stir spot welding parameters of polypropylene - BİLİCİ, MUSTAFA KEMAL (ELSEVIER SCI LTD, 2012)
This paper shows experimental and numerical results of friction stir spot welding of high density polypropylene. The determination of the welding parameters plays an important role for the weld strength. The experimental tests, conducted according to combinations of process factors such as tool rotation speed, plunge depth and dwell time at beginning welding, were carried out according the Taguchi orthogonal table L9 in randomized way. The Taguchi approach was used as a statistical design of experiment technique to set the optimal welding parameters. The results show coherence between the numerical predictions and experimental observations in different cases of weld strength. The signal-to-noise ratio and the analysis of variance were utilized to obtain the influence of the friction stir spot welding parameters on the weld strength. Finally, the improvement in the weld strength from the initial welding parameters to the optimal welding parameters was about 47.7%. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: AUTOMOTIVE APPLICATIONS; STAINLESS-STEEL; SHEETS; PERFORMANCE; DESIGN